Understanding Betawi Culture in Jakarta People Through the Implementation of the Betawi Lebaran Event - Yanna Petricia (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2022)
Betawi culture has a very important role as the original identity of Jakarta city. Globalization and multicultural in Jakarta increasingly erodes the culture of Betawi. Event Lebaran Betawi is presented to educate and provide cultural understanding of Betawi to the people of Jakarta. The purpose of this research is to find out how far the cultural understanding of Betawi gained by Jakarta community from the implementation of the Event Lebaran Betawi 2014. The main theory used in this research is propaganda Lasswell theory and his communication concepts. The method used is descriptive qualitative. Results of this study explained that the implementation of the Event Lebaran Betawi can provide insight of Betawi culture to the people of Jakarta so that the purpose of organizing this event as media education and Betawi culture preservation can be achieved.